x

^{3}=xx^{3}=x

Tutors, please sign in to answer this question.

Lynchburg, VA

Solve for zero to get

x^{3 }- x = 0

factor out an x to get

x(x^{2 }- 1) = 0

Now factor what is in the parenthesis by using the difference of squares rule:

so

x(x - 1)(x +1) = 0

now solve for all three answers (separate the factors and set them ALL = 0)

x = 0 , x - 1 = 0 , x + 1 = 0

when you solve these three you get x = 0, x = 1, and x = -1

Bill Fanning

El Paso, TX

Ronniel M.

Making Math Easy- SAT Prep, Algebra, Precalculus, English, Spanish

Clifton, NJ

5.0
(161 ratings)

Dana R.

English/Math SAT PrepTutor with PhD

Lynbrook, NY

4.8
(85 ratings)

Kathleen D.

Middle and high school math tutor

Franklin Square, NY

5.0
(11 ratings)

- Algebra 4463
- Algebra Help 933
- Algebra 1 3618
- College Algebra 950
- Algebra Word Problem 2251
- Algebra Question 219
- Math 8257
- Algebra 2 3069
- Math Help 4714
- Algebra 2 Question 467